ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK DI BANDAR UDARA INTERNASIONAL SYAMSUDIN NOOR BANJARMASIN - Normajatun Normajatun; Abdul Haliq (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2019)
This study aimed to find out the description: the quality of public services in the Syamsudin Noor airport, Banjarmasin and International factors that can provide community satisfaction on quality public services at the  Syamsuddin  Noor Airport Banjarmasin. Research methods using method survey with quantitative  approach. The population was prospective passenger aircraft were waiting for departure  at the  Syamsuddin Noor Airport Banjarmasin. The design of data collecti  the technique of Importance Performance Analysis (IPA). The results showed the quality of public services in the Syamsudin Noor Airport in Banjarmasin categories either. Then the factors of the quality public services that can provide satisfaction of society described in diagram cartesius. From the diagram, there are two important,  part deserving attention in handling, i.e. the factors contained in the quadrants A, which in this quadrant needs to get top priority for repairs in the future. Besides the factors contained in quadrant B that should have retained its performance going forward.